2010
DOI: 10.1038/npre.2010.4667.1
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Multivariate Serum Profile for Epithelial Ovarian Cancer Using a Prospective Multi-Site Collection

Abstract: In previous studies we described the use of a retrospective collection of ovarian cancer and benign disease samples, in combination with a large set of multiplexed immunoassays and a multivariate pattern recognition algorithm, to develop an 11-biomarker classification profile that is predictive for the presence of epithelial ovarian cancer. In this study, customized, Luminex-based multiplexed immunoassay kits were GMP-manufactured and the classification profile was refined from 11 to 8 biomarkers (CA-125, epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…This assured sample quality and removed the possibility of any collection, processing or biological biases in the sample set, a concern for many other studies [30] . No normal healthy samples were used in this study, as they are typically easier to classify than benign conditions [21] and introduce confounding factors such as lower stress levels compared to patients facing surgery [38] . As expected, the median patient age was higher in individuals with ovarian cancer (61 years) than those with benign conditions (51 years) and increased with the stage of disease present ( Table 1 ; [28] , [36] ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This assured sample quality and removed the possibility of any collection, processing or biological biases in the sample set, a concern for many other studies [30] . No normal healthy samples were used in this study, as they are typically easier to classify than benign conditions [21] and introduce confounding factors such as lower stress levels compared to patients facing surgery [38] . As expected, the median patient age was higher in individuals with ovarian cancer (61 years) than those with benign conditions (51 years) and increased with the stage of disease present ( Table 1 ; [28] , [36] ).…”
Section: Resultsmentioning
confidence: 99%
“…Sera were from a prospective collection undertaken by Correlogic Systems, Inc. specifically to develop and validate the performance of an ovarian cancer test [21] . All samples were collected under a uniform protocol from 11 different sites, which were monitored for adherence.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a similar approach, Wittekind and colleagues reported a set of proteins as biomarker candidates associated with hepatocellular carcinoma [20]. Nowadays, several studies have been performed and focused on biomarker identification in several oncological pathologies; for example: In ovarian cancer, 11 proteins have been identified by Amonkar et al [21]; Sreekumar et al identified a panel of proteins as biomarker candidates in colon carcinoma cells [22]; Díez et al has identified differentially expressed proteins in B-cell chronic lymphocytic leukemia which are related with target therapeutics [23]. Previously, Below and coworkers have developed an antibody microarray to immunophenotype 1100 leukemia and lymphomas according to the abundance of a panel of 82 antigens or cluster of differentiation (CD) characterized at the surfaces of lymphocytes [24].…”
Section: Oncology Diseases-specific Biomarkersmentioning
confidence: 99%